Pengaruh Pemahaman Agama Islam Terhadap Produktivitas Masyarakat di Kecamatan Kuranji Kota Padang - Eka Putra, Doni (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2022)
This type of research is field research with a source of field survey data, namely asking PKH beneficiaries to fill the research instruments. This data is processed based on quantitative analysis looking for correlation values between two variables using the SPSS 16.0 statistical application. After processing the data, the results of the correlation of 0.516 are greater than the correlation value of the table (r-table), the significance level of 5% is 0.1996. In accordance with the hypothesis that r-count is greater than r-table, H1 is accepted, namely there is a significant relationship between the level of understanding of Islam to the productivity of the community. The results of this study clearly illustrated that the level of understanding of Islam influenced the productivity of the people in the Kuranji Subdistrict, Padang City. In accordance with the doctrine and theory of religion that religion has influences that are interconnected with economic behavior, especially in terms of the productivity of society. The low level of understanding of Islam will also be low productivity of the community and vice versa. although between these two variables has a weak relationship but has an influence relationship between the two.